Unveiling Hidden Aspects of Intermediary Organizations in Innovation: A Systematic Review through the Lens of Industry Taxonomy - Mostafa Mohseni kiasari; ‌Javad Soltanzadeh; Amirhossein Azizi Hasanabadi; Hamed Talebi (مدیریت صنعتی)
Objective In the innovation system, actors are involved in a complex situation of formal and informal networks, both within and among subgroups. The unsteady interactions between the actors make the role of intermediaries important. Intermediary organizations in the innovation system try to assume functions based on the deficiencies in the interactions. The functions of intermediary institutions have been examined from various aspects in various articles and studies. The diversity stems from communication gaps and inherent shortcomings among the interacting parties within the innovation system. Although studies provide a list of these functions, how to guide these intermediate actors of the innovation system and determine their appropriate functions in a reflection of the characteristics of the industry is still questioned by innovation policymakers. Especially, the nature of innovation and the technological regime of the industries have substantial differences. The current research aimed to provide a comprehensive definition of the current knowledge and the classification of intermediary institutions in industries by Poit (1984) based on the definitional functions of Howells (2006) and also to create an interpretation of the existing research gaps.